Historic mosques in Sub-Saharan Africa : from Timbuktu to Zanzibar - Pradines, Stéphane (Handbook of Oriental studies. Near and Middle East (2014), 2022)
"This book is the first comprehensive synthesis on mosques in sub-Saharan Africa, bringing together sites from more than twenty states from sub-Saharan Africa; and more than 285 monuments, from the IXth to the XIXth centuries. This monograph is divided into three large geographical areas, from the earthen mosques of West Africa, to the Nile Valleys and the Horn of Africa, and to the Indian Ocean shores and Swahili coral stone mosques. This book is a statement that African mosques demonstrate cultural links with North Africa, Arabia, Persia and India, these monuments are unique in the history of Islamic architecture, and they belong to our World Heritage"--